The Influence of Transformational Leadership Style on Job Satisfaction and Employee Performance at the Arifah Gowa Foundation - Supriadi; Sitti Nurbaya; Zalkha Soraya (GoodWill, 2026)
This study aims to examine the influence of transformational leadership style on job satisfaction and employee performance at the Arifah Gowa Foundation. The research adopts a quantitative approach using a survey method involving 90 employees selected through a saturated sampling technique. Data were collected using structured questionnaires based on a Likert scale and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. The results indicate that transformational leadership has a positive and significant effect on job satisfaction, as evidenced by a t-statistic value of 7.555 and a p-value below 0.05. Furthermore, job satisfaction significantly influences employee performance with a t-statistic value of 6.360. Transformational leadership also directly affects employee performance (t-statistic = 2.633; p < 0.05). In addition, job satisfaction mediates the relationship between transformational leadership and employee performance, demonstrating an indirect significant effect (t-statistic = 3.843; p < 0.05). These findings highlight that transformational leadership plays a crucial role in enhancing employee performance both directly and indirectly through increased job satisfaction. The study contributes to the literature by providing empirical evidence within the context of an educational foundation, which remains relatively underexplored. Practically, the results suggest that organizational leaders should adopt transformational leadership practices to improve employee satisfaction and optimize performance outcomes.